Complications of Percutaneous Coronary Interventions - Butman, Samuel M. (Springer New York : Imprint: Springer, 2005)
Percutaneous coronary catheterization has become one of the most common medical interventions performed in the field of interventional cardiology. With the continual technical improvements in interventional cardiology, more procedures are being performed and higher risk patients are being treated. Complications are bound to occur, and when they do, they are distressing to the clinician. Too often, clinicians performing an interventional procedure are unprepared and lack complete familiarity with some of the possible adverse events or the many creative methods available to them to reverse or mitigate the event. This book provides the reader with a valuable overview of the complications associated with coronary interventions. The editor, Samuel M. Butman, MD, has assembled a group of contributors renowned for their expertise in interventional cardiology. Chapters are concise but comprehensive and present actual case examples for review. Topics covered include complications related to medication, coronary guidewires, coronary stenting, atherectomy devices, and radiation exposure. Useful illustrations reinforce key concepts. Complications of Percutaneous Coronary Interventions fills a void for interventional cardiologists, residents, and technologists who need to learn about effectively preventing complications or who simply want to more confidently institute appropriate treatment.